Enhanced degradation performance of Ag-loaded BiOI composite photocatalysts for water pollutant removal - Chen Cong; Wang Shenghong; Wang Jiayuan; Sun Changfei; Li Denghui; Zhai Zhenjie (Discover Applied Sciences)
Abstract Composite photocatalyst materials have potential application value in the field of environmental protection, especially in the degradation of water pollutants. In this paper, Ag-BiOI composite photocatalyst materials were prepared by deposition method on BiOI flower-like microspheres prepared by microwave solvothermal method. BiOI flower balls are stacked by interlaced nanosheets, and Ag nanoparticles are attached to the surface of BiOI microspheres. This paper explores the effect of Ag loading on the photocatalytic performance of composite materials through variable control. The research results show that as the Ag content increases, the degradation rate of RhodamineB (RhB) and Ciprofloxacin (CIP) of the sample under visible light irradiation increases. The 4% Ag/BiOI composite photocatalyst exhibits the best degradation performance for Rhodamine B solution (RhB, 20 mg/L) and Ciprofloxacin solution (CIP, 10 mg/L), achieving degradation rates of 80.4% and 80.0%, respectively, which is five times higher than that of BiOI before loading. This significantly improves the treatment efficiency of organic pollutants.In addition, excessive Ag particle compounding will reduce the light absorption performance of the sample, thereby reducing the catalytic degradation characteristics of the material. Furthermore, the recyclability of the 4% Ag-BiOI composite was evaluated, and it was found that after five cycles of use, the photocatalytic activity remained stable, indicating excellent reusability of the material. Finally, this article discusses the catalytic degradation mechanism of Ag composite catalyst materials based on experimental results, and provides a design strategy for loading heavy metals to improve the catalytic performance of materials.